Growing Through Labor-Implementation of a Gamified Tea Learning Curriculum in Kindergarten - Gao, Yun (Journal of Educational Research and Policies, 2025)
Labor education is essential for student growth, nurturing both physical and mental well-being. Early childhood education, primarily based on games, can stimulate interest in labor, cultivate skills, and foster enthusiasm for work through familiar and engaging games. This article, based on an analysis of the current state of early childhood labor education, uses gamified instruction within the theoretical framework of the tea science curriculum: learning through tea belts, preparing and tasting tea, integrating tea tasting, and retaining and tasting tea. This approach aims to help preschoolers develop a sense of labor and habits, increase their understanding of traditional Chinese tea, strengthen their coordination, and enhance their aesthetic appreciation.